Queenan's Management of High-Risk Pregnancy : An Evidence-Based Approach - Queenan, John T.; Spong, Catherine Y.; Lockwood, Charles J. (Chichester : Wiley-Blackwell, 2012)
For the maternal-fetal physician, constant vigilance throughout a pregnancy remains essential. But continuous change makes this an increasing challenge. Queenan's Management of High-Risk Pregnancy covers the full spectrum of perinatal care. Providing evidence, algorithms, and case studies, this book guides you through the tough and complex decisions needed to protect the health of both your fetal and the maternal patients. New material in the 6th edition covers contemporary issues such as, iron-deficient anemia, malaria, pregnancy in the disabled woman, placenta accrete, induction of labor, op.
Front Matter -- Colour Plates -- Factors of High-Risk Pregnancy. Overview of High-Risk Pregnancy / John T Queenan, Catherine Y Spong, Charles J Lockwood -- Maternal Nutrition / Edward R Newton -- Alcohol and Substance Abuse / William F Rayburn -- Environmental Agents and Reproductive Risk / Laura Goetzl -- Genetics. Genetic Screening for Mendelian Disorders / Deborah A Driscoll -- Screening for Congenital Heart Disease / Lynn L Simpson -- First- and Second-Trimester Screening for Fetal Aneuploidy and Neural Tube Defects / Julia Unterscheider, Fergal D Malone -- Monitoring: Biochemical and Biophysical. Sonographic Dating and Standard Fetal Biometry / Eliza Berkley, Alfred Abuhamad -- Fetal Lung Maturity / Alessandro Ghidini, Sarah H Poggi -- Antepartum Fetal Monitoring / Brian L Shaffer, Julian T Parer -- Interpreting Intrapartum Fetal Heart Tracings / Michael Nageotte -- Maternal Disease. Sickle Cell Anemia / Scott Roberts -- Anemia / Alessandro Ghidini -- Thrombocytopenia / Robert M Silver -- Inherited and Acquired Thrombophilias / Michael J Paidas -- Thromboembolic Disorders / Christian M Pettker, Charles J Lockwood -- Cardiac Disease / Stephanie R Martin, Alexandria J Hill, Michael R Foley -- Renal Disease / David C Jones -- Pregnancy in Transplant Patients / James R Scott -- Gestational Diabetes Mellitus / Deborah L Conway -- Diabetes Mellitus / George Saade -- Hypothyroidism and Hyperthyroidism / Brian Casey -- Asthma / Michael Schatz -- Epilepsy / Autumn M Klein, Page B Pennell -- Chronic Hypertension / Heather A Bankowski, Dinesh M Shah -- Systemic Lupus Erythematosus / Christina S Han, Edmund F Funai -- Perinatal Infections / Jeanne S Sheffield -- Malaria / Richard M K Adanu -- Group B Streptococcal Infection / Ronald S Gibbs -- Hepatitis / Patrick Duff -- HIV Infection / Howard L Minkoff -- Pregnancy in Women with Physical Disabilities / Caroline C Signore -- Obstetric Complications. Recurrent Spontaneous Abortion / Charles J Lockwood -- Cervical Insufficiency / John Owen -- Gestational Hypertension, Preeclampsia, and Eclampsia / Labib M Ghulmiyyah, Baha M Sibai -- Postpartum Hemorrhage / Michael A Belfort -- Emergency Care / Garrett K Lam, Michael R Foley -- Rh and Other Blood Group Alloimmunizations / Kenneth J Moise -- Multiple Gestations / Karin E Fuchs, Mary E D'Alton -- Polyhydramnios and Oligohydramnios / Ron Beloosesky, Michael G Ross -- Prevention of Preterm Birth / Paul J Meis -- Pathogenesis and Prediction of Preterm Delivery / Catalin S Buhimschi, Charles J Lockwood -- Preterm Premature Rupture of Membranes / Brian M Mercer -- Management of Preterm Labor / Vincenzo Berghella -- Placenta Previa and Related Placental Disorders / Yinka Oyelese -- Complications of Labor and Delivery. Prolonged Pregnancy / Teresa Marino, Errol R Norwitz -- Induction of Labor / Nicole M Petrossi, Deborah A Wing -- Cesarean Delivery / Michael W Varner -- Vaginal Birth after Cesarean Delivery / Mark B Landon -- Breech Delivery / Edward R Yeomans, Larry C Gilstrap -- Operative Vaginal Delivery / Edward R Yeomans -- Obstetric Analgesia and Anesthesia / Gilbert J Grant -- Patient Safety / Christian M Pettker -- Neonatal Encephalopathy and Cerebral Palsy / Maged M Costantine, Mary E D'Alton, Gary D V Hankins -- Procedures. Genetic Amniocentesis and Chorionic Villus Sampling / Ronald J Wapner -- Fetal Surgery / Robert H Ball, Hanmin Lee -- Index.
Revised edition of: Management of high-risk pregnancy / edited by John T. Queenan, Catherine Y. Spong, Charles J. Lockwood. 5th. 2007.
Includes bibliographical references and index.
Print version record.
Keywords: Pregnancy -- Complications; Pregnancy Complications; Evidence-Based Medicine; Pregnancy, High-Risk.; Evidence-Based medicine; Placenta accrete; Pregnancy -- Complications; Pregnancy complications; Pregnancy, High-Risk.; Medicine; MEDICAL -- Gynecology & Obstetrics; Pregnancy -- Complications; Electronic books; Electronic books